(3cfR GdOQQs - (3CHh HcQ YHO Gddg Hf CjHc GdOhGOGQjs
(3ChdgG (B:s
(3GdMeO ddg GdPi EQJVi (B( (3GdMeO (B) (3ef YHGOg CcQege hCTQbge hHYO aEf GdYHO JbOe efg Gdbhd HMhd Pi GdbhI hGdWhd ajeG eVi ai GdLRA GdChd hGdKGfi hGdKGdK , eeG jdgi eJCedge Yf SeGY GdeKGfi hGdeKGdH , deG bO EMJhhYdjg ef ZQGFH GdCNHGQ s
(3BNQgG (B:s
(3hGddjd CWhd TF Mjf CabOgG hGddjd CbUQ TF Mjf CdbGgG GfJgi Gdbhd ai PcQ GdTYQGA hGdePchQjf hHJeGege Je GdLRA GdKGdK ef GdJGQjN GdeSei cfR GdOQQ hLGeY GdZQQ s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs